Les dépendances vertes dans les paysages agricoles : prendre en compte les milieux adjacents à la route - Francesca Di Pietro; Clémence Chaudron; Rémi Perronne (VertigO)
Transportation infrastructures are usually considered as damaging for biodiversity because of their barrier effect. However, through their vegetative verges, these infrastructures can also enhance biodiversity as corridors or refugia for many species. These contradictory effects of transportation infrastructures on biodiversity have been studied mainly for road networks, one of the main components of landscape fragmentation. In this study, we focused on the connectivity between roadside verges and adjacent arable fields for herbaceous plants within a cereal farming landscape characterized by a gradient of forest fragmentation. This narrow boundary is intensively managed, both by local authority services, implementing delayed mowing, and by farmers. The management regimes of this roadside vegetation could have contrasting effects on plant diversity of verges and arable field margins, and also be the cause of conflicts between local authorities and farmers. If alternative management applied on these verges fails to take into account potential effects on the adjacent arable fields, such conflicts could concern other transportation infrastructures in agricultural landscapes.